Different doses of Dexmedetomidine in attenuating the pressor response to laryngoscopy in controlled hypertensive patient under general anesthesia (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Laryngoscopic manipulation and endotracheal intubation are always a matter of concernwhich capable of producing tachycardia, arrhythmias and hypertension which is generally well tolerated inhealthy patient. In Hypertensive patient cardiovascular response to laryngoscopy and intubation is exaggerated.Aims: To assess the effectiveness in attenuation of haemodynamic responses to laryngoscopy andendotracheal intubation with different doses of intravenous dexmedetomidine in controlled hypertensivepatients with no adverse effects.Methods: This prospective Randomized controlled trial was carried out with 60 patients belonging toAmerican Society of Anesthesiologists (ASA) Physical Status II posted for elective general anaesthesia.Patients were randomly divided into three groups with fixed card sampling, where, patients who receivedIV dexmedetomidine 0.5 μg/kg diluted to 50 ml with normal saline as infusion over 10 min was consideredas group A, patients who received IV dexmedetomidine 0.75 μg/kg diluted to 50 ml with normal salinewas considered as group B and patients who received IV dexmedetomidine 1 μg/kg diluted to 50 ml withnormal saline was considered as group C. The primary outcome measures were haemodynamic responseat 1, 3 and 5 min after intubation. The secondary outcome measures were to note down any adverseeffects associated with drugs.Result: The groups were well matched for their demographic data . Male to female ratio was 1:1 in allthree group. The mean height, weight and BMI were almost similar among three groups. In this studybaseline readings of SBP, DBP, MAP and HR were almost similar in all three groups and statistically notsignificant. Maximum intubation response was seen at 1 min post intubation in all the three groups. Themean SBP of group A varied from 144.8±8.4 mmHg to 118.5±4.4 mmHg that of group B varied from134.8±4.1 to 122.0±4.2 mmHg and then group C varied from 126.5±15.5 mmHg to 103.8±8.4 mmHgduring different evaluation period (p